Classroom language during COVID-19: Associations between mask-wearing and objectively measured teacher and preschooler vocalizations - Mitsven, Samantha G.; Perry, Lynn K.; Jerry, Christian M.; Messinger, Daniel S. (Frontiers in Psychology, 2022)
During the COVID-19 pandemic, mask-wearing in classrooms has become commonplace. However, there is little data on the effect of face-masks on children’s language input and production in educational contexts, like preschool classrooms which over half of US children attend. Leveraging repeated objective measurements, we longitudinally examined child and teacher speech-related vocalizations in two cohorts of 3.5-4.5-year-old children enrolled in the same oral language classroom that included children with and without hearing loss. Cohort 1 was observed before COVID-19 (no face-masks, N=20) and Cohort 2 was observed during COVID-19 (with face-masks; N=15). Vocalization data were collected using child-worn audio recorders over 12 observations spanning two successive school years, yielding 9.09 mean hours of audio recording per child. During COVID-19 teachers produced a higher number of words per minute than teachers observed prior to COVID-19. However, teacher vocalizations during COVID-19 contained fewer unique phonemes than teacher vocalizations prior to COVID-19. Children observed during COVID-19 did not exhibit deficits in the duration, rate, or phonemic diversity of their vocalizations compared to children observed prior to COVID-19. Children observed during COVID-19 produced vocalizations that were longer in duration than vocalizations of children observed prior to COVID-19. During COVID-19 (but not before), children who were exposed to a larger number of words per minute from teachers produced more speech-related vocalizations per minute themselves. Overall, children with hearing loss were exposed to teacher vocalizations that were longer in duration, more teacher words per minute, and more phonemically diverse teacher speech than children with typical hearing. In terms of production, children with hearing loss produced vocalizations that were longer in duration than the vocalizations of children with typical hearing. Among children observed during COVID-19, children with hearing loss exhibited a higher vocalization rate than children with typical hearing. These results suggest that children’s language production is largely unaffected by mask use in the classroom and that children can benefit from the language they are exposed to despite teacher mask-wearing.